2020
DOI: 10.1049/iet-stg.2019.0005
|View full text |Cite
|
Sign up to set email alerts
|

Energy management system for residential buildings based on fuzzy logic: design and implementation in smart‐meter

Abstract: Advances in distributed generation and increased contribution of renewable energy source (RES) require development of smart grid technologies. Smart metering systems, as a part of smart grid technologies, in cooperation with modern buildings equipped with building management system allows for improvement of energy efficiency. It is possible to partially cover the power demand of a building from the local RESs. However, in order to ensure maximum added value, energy management system (EMS) is essential. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…A similar rule-based architecture using defeasible logic was also implemented by Cristani, Tomazzoli, Karafili, and Olivieri (2016). Chojecki et al (2020) designed a system that combined a rule-based implementation along with a fuzzy logic algorithm, incorporated on a smart meter to perform direct control. Last, Papaioannou et al (2018) proposed an event-based rule engine to change energy waste behaviors in public buildings.…”
Section: Rule Enginementioning
confidence: 99%
“…A similar rule-based architecture using defeasible logic was also implemented by Cristani, Tomazzoli, Karafili, and Olivieri (2016). Chojecki et al (2020) designed a system that combined a rule-based implementation along with a fuzzy logic algorithm, incorporated on a smart meter to perform direct control. Last, Papaioannou et al (2018) proposed an event-based rule engine to change energy waste behaviors in public buildings.…”
Section: Rule Enginementioning
confidence: 99%
“…Recently, many research contributions proposed different designs of smart energy meters for home automation and smart building management [9,22]. Sayed et al, in reference [22], suggested a smart meter prototype design based on knowledge of integration of university-level educational courses.…”
Section: Related Workmentioning
confidence: 99%
“…Different from above, in [71], an SM is designed using the fuzzy logic with the objective of minimizing the consumers cost of energy provided with an increased security. The SM's design contains the traditional LCD (liquid crystal display), buttons, power supply, and serial port modules with the WiFi connectivity.…”
Section: ) Smart Metering and Energy Management In Buildings/homesmentioning
confidence: 99%